Kinematic and kinetic performance variables during paddling among para-kayak athletes with unilateral above or below knee amputation - Rosen, J. S.; Arndt, A.; Nilsson, J.; Rosdahl, H.; Goosey-Tolfrey, V. L.; Bjerkefors, A. (Sports Biomechanics, 2022)
In para-kayak, athletes with unilateral above knee amputation (AK) and athletes with below knee amputation (BK) compete in the same class. This has been questioned since previous research have shown that the legs are important for paddling performance. The purpose was therefore to examine differences in kinematic and kinetic performance variables between AK and BK para-kayak athletes and the amputated (A) and non-amputated (NA) sides. Eleven AK and six BK athletes on international level participated. 3D kinematic and kinetic data were collected for the body, seat, footrest and paddle during kayak ergometer paddling. There were no significant differences between the groups in main performance variables such as power output or paddle force. Differences between the groups were only seen in the hip joint in flexion range of motion, flexion and extension angular velocity and flexion moment where BK demonstrated larger values. The NA side demonstrated greater values compared to the A side in posterior force at the seat and in hip flexion moment. As there were no significant differences between the groups in the majority of the examined key performance variables, the results suggest that athletes with unilateral AK and BK amputation may be able to compete in the same class.